Evapotranspiration Partition and Dual Crop Coefficients in Apple Orchard with Dwarf Stocks and Dense Planting in Arid Region, Aksu Oasis, Southern Xinjiang - Hui Cao (MDPI AG, 2021)
Crop coefficients are critical to developing irrigation scheduling and improving agricultural water management in farmland ecosystems. Interest in dwarf cultivation with high density (DCHD) for apple production increases in Aksu oasis, southern Xinjiang. The lack of micro-irrigation scheduling limits apple yield and water productivity of the DCHD-cultivated orchard. A two-year experiment with the DCHD-cultivated apple (Malus × domestica ‘Royal Gala’) orchard was conducted to determine crop coefficients and evapotranspiration (ETa) with the SIMDualKc model, and to investigate apple yield and water productivity (WP) in response to different irrigation scheduling. The five levels of irrigation rate were designed as W1 of 13.5 mm, W2 of 18.0 mm, W3 of 22.5 mm, W4 of 27.0 mm, and W5 of 31.5 mm. The mean value of basal crop coefficient (Kcb) at the initial-, mid-, and late-season was 1.00, 1.30, and 0.89, respectively. The Kc-local (ETa/ET0) range for apple orchard with DCHD was 1.11–1.20, 1.33–1.43, and 1.09–1.22 at the initial, middle, and late season, respectively. ETa of apple orchard in this study ranged between 415.55–989.71 mm, and soil evaporation accounted for 13.85–29.97% of ETa. Relationships between total irrigation amount and apple yield and WP were developed, and W3 was suggested as an optimum irrigation schedule with an average apple yield of 30,540.8 kg/ha and WP of 4.45 kg/m3 in 2019–2020. The results have implications in developing irrigation schedules and improving water management for apple production in arid regions.